In silico Validation of Pseudomonas aeruginosa Exotoxin A Domain I Interaction with the Novel Human scFv Antibody - Shadman, Zahra; Ghasemali, Samaneh; Farajnia, Safar; Mortazavi, Mojtaba; Biabangard, Atefeh; Khalili, Saeed; Rahbarnia, Leila (Infectious Disorders - Drug Targets, 2023)
Background: Pseudomonas (P.) aeruginosa is one of the leading causes of nosocomial infections. The pathogenicity of P. aeruginosa is related to its inherent antimicrobial resistance and the diverse virulence factors of this bacterium. Owing to the specific role of exotoxin A in P. aeruginosa pathogenesis, it is known as a promising therapeutic candidate to develop antibodies as an alternative to antibiotics. Objective: The present study aimed to validate the interaction between a single-chain fragment variable (scFv) antibody identified from an scFv phage library against domain I exotoxin A by bioinformatic tools. Methods: For this, several bioinformatics tools, including Ligplot, Swiss PDB viewer (SPDBV), PyMOL, I-TASSER, Gromacs, and ClusPro servers were used to evaluate the interaction of scFv antibody with P. aeruginosa exotoxin A. The I-TASSER server was utilized to predict the function and structure of proteins. The interaction of two proteins was analyzed using ClusPro tools. The best docking results were further analyzed with Ligplot, Swiss PDB viewer, and PyMOL. Consequently, molecular dynamics simulation was utilized to predict the stability of the secondary structure of the antibody and the binding energy of the scFv antibody to the domain I of exotoxin A. Results: As a result, we demonstrated that data from computational biology could provide proteinprotein interaction information between scFv antibody/domain I exotoxin A and offers new insights into antibody development and therapeutic expansion. Conclusion: In summary, a recombinant human scFv capable of neutralizing P. aeruginosa exotoxin A is recommended as a promising treatment for infections caused by P. aeruginosa.
Keywords: P. auroginosa